The formation of foreign - language abilities as a basis of a foreign language training individualization of future engineer-teachers. - Zelenin, G. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the question of foreign-language abilities forming as a basis of a foreign language training individualization of future engineer-teachers. The author tries to define the concept individual approach, allocate some types of educational process individualization, taking into consideration the characteristics of substructures of psychological student’s structure in the methods of foreign language teaching and to define effective methods of their realization, articulates the concept of abilities and defines the principles of a foreign language teaching process in engineer pedagogical higher educational establishments, oriented to the foreign-language abilities forming. The article deals with the question of what pedagogical functions are performed by the training process, constructed on individual approach and why there is a burning reason to apply an individual approach in the training process of a foreign language in engineer-pedagogical higher educational establishment.